2009
DOI: 10.1063/1.3080248
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric relaxation mechanisms of BiMn2O5 ceramics

Abstract: Dielectric properties of multiferroic BiMn2O5 ceramics were evaluated over broad temperature and frequency ranges. Two Debye-type dielectric relaxations were observed at low temperatures (130–250 K) and high temperatures (200–450 K), respectively. The low temperature relaxation with an activation energy of 0.18 eV was attributed to charge carrier hopping process between Mn3+ and Mn4+. The high temperature dielectric relaxation with an activation energy of 0.38 eV, which is similar to the activation energy of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…However, a detailed study of the relaxor behavior could not be appropriately done, due to the few measured points of frequency and narrow temperature range. In a recent article, Lin et al 29 have addressed this problem again, using polycrystalline samples of BiMn 2 O 5 and measuring dielectric constant in a broad temperature (123 K to 523 K) and frequency (1 Hz to 10 MHz) ranges. They also have found evidence of relaxor behavior, but ruled out this possibility, since the peak temperature obeyed the Arrhenius behavior rather than the Vogel-Fulcher relation.…”
mentioning
confidence: 99%
“…However, a detailed study of the relaxor behavior could not be appropriately done, due to the few measured points of frequency and narrow temperature range. In a recent article, Lin et al 29 have addressed this problem again, using polycrystalline samples of BiMn 2 O 5 and measuring dielectric constant in a broad temperature (123 K to 523 K) and frequency (1 Hz to 10 MHz) ranges. They also have found evidence of relaxor behavior, but ruled out this possibility, since the peak temperature obeyed the Arrhenius behavior rather than the Vogel-Fulcher relation.…”
mentioning
confidence: 99%
“…On the other hand inclusions with higher conductivity than that of the matrix will also result interfacial or Maxwell-Wagner-Sillars polarization which has a major influence in the acoustic frequency regime, i.e., 10 Hz-1 MHz. Thus it is not expected to have a major contribution in the results especially due to stable characteristics as a function of frequency [11,12]. Therefore the effect is expected to be result of addition of nanosize particles with large specific surface area.…”
Section: Discussionmentioning
confidence: 99%
“…Typically a high fractional amount of inorganic is required to obtain a significant increase in permittivity thus reducing drastically the processability and mechanical ruggedness of the material [1,[5][6][7][8][9]. Obtaining high effective permittivity and low losses is especially challenging at high frequencies due additional decrement of the permittivity as a function of frequency caused by dielectric relaxation [10][11][12]. Very high dielectric constants have been experimented at low frequencies with Ni-PVDF composites (ε r ∼ 400, tan δ > 0.15 at 100 Hz) [13].…”
Section: Introductionmentioning
confidence: 99%
“…The pyroelectric current changed its sign with switching the direction of the poling field of the polycrystalline material [34]. The investigations of dielectric properties of BiMn 2 O 5 revealed high dielectric constant [35] in the range of 10 5 e10 6 at room temperature, which is promising for applications in capacitors. The studies of frequency dependence of the dielectric constant revealed [35] a low temperature dielectric relaxation, attributed to the hopping of charge between Mn 3þ and Mn 4þ , and high temperature dielectric relaxation, related to oxygen defects.…”
Section: Introductionmentioning
confidence: 96%
“…The investigations of dielectric properties of BiMn 2 O 5 revealed high dielectric constant [35] in the range of 10 5 e10 6 at room temperature, which is promising for applications in capacitors. The studies of frequency dependence of the dielectric constant revealed [35] a low temperature dielectric relaxation, attributed to the hopping of charge between Mn 3þ and Mn 4þ , and high temperature dielectric relaxation, related to oxygen defects. The analysis of the dielectric constant at different conditions [33] suggested a relaxor type ferroelectric behavior at high temperatures.…”
Section: Introductionmentioning
confidence: 97%